Pemuda dalam Mengembangkan Social Entrepreneurship - Susanti, Susi; Kisworo, Bagus (Journal of Nonformal Education and Community Empowerment, 2021)
This research aims to describe the involvement of youth in developing social entrepreneurship pottery in Gebangsari Village, Klirong District, Kebumen Regency andthe factors inhibiting the involvement of youth in developing social entrepreneurshippottery. This study uses a qualitative approach. Data collection techniques in the form ofobservations, interviews, and documentation. While data analysis techniques are carriedout with data reduction, data presentation, and conclusion drawing. The results of theresearch obtained that the involvement of gebangsari youth in developing socialentrepreneurship pottery is still minimal involvement of youth. Factors that hinder youthin participating in the wirausaahaan pottery are internal factors in the form ofmotivation factors, readiness factors, and talent factors, while external factors in the formof family environment and community environment.